Systematic Systematic Literature Riview Dampak COVID-19 pada Pelayanan Imunisasi Bayi: 1. Pendahuluan, 2. Metode, 3. Hasil dan Pembahasan, 4. Penutup dan Kesimpulan - Sri Chalada; Indang Trihandini (2023)
The consequences of COVID-19 response measures such as restrictions on mobilization (Lockdown) have an impact on infant immunization services in the world, especially in lower and middle-income countries experiencing a decrease in coverage, therefore this study aims to examine the impact of COVID-19 on immunization services. baby. The research method uses a systematic literature review following the PRISMA rules. Search for scientific articles through the Proquest, Scince Direct and Scopus databases for 2019-2022. Initially obtained 11,437 articles, after screening only 27 articles that met the criteria. From the results of the study, it was found that the impact of COVID-19 on Vulnerable infant immunization services decreased by 6-52.5% in all countries. types of vaccines affected by DPT, BCG and MMR. Some of the causes of the decline in immunization coverage include fear of COVID-19 so they are reluctant to visit, difficult access such as in rural areas and other factors. Suggestions from this study strengthen services such as system recovery, improve access with logistical support. appointments to catch up, use technology appropriately, service providers use communication strategies in service so that parents or guardians avoid worries